Ecologies of Affect : Placing Nostalgia, Desire, and Hope - Davidson, Tonya K., 1979-; Park, Ondine, 1974-; Shields, Rob, 1961- (Book collections on Project MUSE., 2011)
Ecologies of Affect offers a synthetic introduction to the felt dynamics of cities and the character of places. The contributors capture the significance of affects, including desire, nostalgia, memory, and hope, in forming the identity and tone of places. The critical intervention this collection of essays makes is an active, consistent engagement with the virtualities that produce and refract our idealized attachments to place. Contributors show how place images and attempts to build communities are not abstractions but are fundamentally tied to and resolve around such intangibles. We understand nostalgia, desire, and hope as virtual; that is, even though they are not material, they are nonetheless and must be accounted for. In this book, the authors take up affect, emotion, and emplacement and consider them in relation to one another and how they work to produce and are produced by certain temporal and spatial dimensions.